The effectiveness of a water resource tax policy in improving water-use efficiency: a quasi-natural experiment-based approach. Issue 6 (19th May 2022) - Mu, Lan; Zhang, Xiaoyan; Cheng, Sen; Song, Peisong
Abstract: Comprehensively improving the efficiency of water resource utilization is not only an urgent need to resolve the prominent contradiction between water supply and water demand but also an inevitable requirement to promote the harmonious coexistence between humans and nature. The compulsory water resource tax is considered to be a powerful tool for resolving the worldwide water crisis and improving water resource utilization efficiency (WRUE). Based on a quasi-natural experiment of water resource tax policy in China, this study used panel data for 30 provinces (municipalities) from 2011 to 2019 to evaluate the impact of water resource tax policies on WRUE through a multistage difference-in-difference model. The results showed that the water resource policy can effectively improve the utilization efficiency of water resources by optimizing the allocation of resources. In addition, the analysis of the spatial heterogeneity showed that the policy of the water resource tax has a stronger lifting effect on improving water resource-use efficiency in eastern China than that in the central and western regions. This research provided insights into China's water policies that can be used to better manage natural resources. HIGHLIGHTS: A multistage dynamic difference-in-difference (DID) model is applied to test the impact of water resource tax policy. There is temporal variation and spatial heterogeneity of water resource-use efficiency across China. The water resource tax policy has significantly improved water use efficiency. The mechanisms of the policy effect have been explored. Graphical Abstract